Investigating the Effects of Fish Effluents as Organic Fertilisers on Basil (Ocimum basilicum) - Lorenzo Fruscella; Benz Kotzen; Marcos Paradelo Perez; Sarah Milliken (Applied Sciences)
Whilst the potential of fish effluents as nutrient sources for crop production has been demonstrated, their use in the European Union remains prohibited in organic farming. In this study, we investigate the efficacy in greenhouse basil cultivation of two types of fish effluents (filtered ‘fish water’ and unfiltered ‘fish sludge’) from an aquaponic system, and assess their role in maintaining and enhancing soil fertility as well as their potential to create a ’living soil’, which are two of the prerequisites for organic certification in the EU. To evaluate the contribution of fish effluents to plant growth in comparison with soil nutrients, basil plants were grown in pots containing two types of substrate: compost-free (without organic matter) and with compost (with organic matter). The results indicate that fish water and fish sludge demonstrate significant potential as fertilisers and outperform compost in certain parameters, such as plant biomass. The results also align with existing literature by demonstrating the positive impact of compost on soil microbial diversity, underscoring its role in fostering plant health. Although the treatments did not show differences in microbial composition at the genus level, the higher microbial diversity observed following fish effluent application highlights its potential for promoting ’living soil’. This research underscores the need for continued exploration of the implications of compost application in conjunction with fish effluent fertilisation on soil microbial communities and the production of specialty crops such as herbs.